PENGARUH KONTEN TIKTOK @REXI TERHADAP MINAT FOLLOWERS UNTUK MODIFIKASI MOTOR - Lumban Gaol, Richard Kurnadi; Abidin, Sholihul (SCIENTIA JOURNAL, 2024)
One social media platform that is currently quite familiar to Indonesian society is TikTok. TikTok is a social networking platform used to create content in the form of short videos. Someone may become famous on TikTok because of their interesting content; these people are called "tiktokers". One of the most interesting Tiktokers is Rexi. His content has a unique characteristic because he makes motorbike modification videos that his followers are interested in. The research methodology used is a quantitative method that is associative in nature. The sampling technique used in this research is random sampling; The sample consisted of 100 respondents. Research data comes from the results of questionnaires. The data in this study was cleaned using IBM SPSS 25 software. The results of the analysis of Rexi's TikTok account had a positive and significant effect on followers' desire to modify motorbikes. because the value of the influence of the content is significant, 0.000 < 0.05 and the t-calculated value of 15.616 is greater than the t-table value of 1.984, so it can be concluded that H0 is rejected and Ha is accepted